Eating Behaviors in Cuban Adults: Results from an Exploratory Transcultural Study - Rodríguez-Martín, Boris C.; Innamorati, Marco; Imperatori, Claudio; Fabbricatore, Mariantonietta; Harnic, Désirée; Janiri, Luigi; Rivas-Suárez, Saira R. (Frontiers in Psychology, 2016)
This study aims to investigate eating behaviors in Cuban adults and compare them with those of a developed Western country, Italy. The study also aimed to determine the overall accuracy of a predictive model intended to define variables which could be used to discriminate between nationalities. Participants were 283 normal weight individuals from Cuba (n = 158) and Italy (n = 125). Italians had higher scores for restrained eating on the questionnaire than Cubans with a considerable effect size. This trend was also found for emotional eating and binge eating, as well as number of current dieters, despite the fact that effect sizes were small. On the other hand, Cubans, when compared to Italians reported higher scores for food thought suppression with reward responsiveness and restrained eating emerging as significant predictors of between-country differences. To conclude, eating behaviors in Cubans could be different from those reported in European countries, perhaps as a consequence of Cuba’s recent history.